Irrigation of Agricultural Crops with Municipal Wastewater - A Review - Hoogendijk, K.; Myburgh, P.A.; Howell, C.L.; Hoffman, J.E. (South African Journal of Enology and Viticulture, 2023)
Sustainable viticulture is important for socio-economic prosperity in the Western and Northern Cape provinces of South Africa. Limited natural water resources, as well as periodic droughts in these regions necessitate the need to find alternative sources of irrigation water to sustain yield and quality. The large volumes of treated municipal wastewater generated annually holds promise as an alternative water source. Despite various treatment procedures, municipal wastewater may contain high levels of Na+, B3+, Cl- and SO42-, as well as trace elements and heavy metals. However, it often contains essential plant nutrients, e.g. N, P and K+. If treated properly, municipal wastewater may be beneficial when reused for irrigating agricultural crops. Possible benefits include recycling of nutrients, fertiliser savings, the addition of organic material, a reduced pressure on fresh water sources and reduced environmental contamination. However, high salt loads, in particular Na+, can have detrimental effects on soil physical and chemical properties, as well as crop sustainability. Therefore, it is essential to implement measures that will limit damage caused by salinity and/or sodicity. The attenuation and accumulation of toxic substances should also be managed to a minimum. Most of the information regarding treated municipal wastewater has been generated through laboratory studies using simulated wastewater, or in some cases actual wastewater. No studies have yet investigated the impact of irrigation with treated municipal wastewater under the conditions that prevail in South African grape growing regions.